Ramifications of Divorce by Dayak Customary Law: Exploring Legal Consequences in Indonesian Legal System - Kurniawan, Itok Dwi; Septiningsih, Ismawati; Santos, Jose Gama (Universitas Negeri Semarang, 2024)
This research explains the consequences of divorce according to the laws of the Dayak traditional community in Central Kalimantan province. The research method used is normative using primary and secondary legal materials. Customary law is one of the laws recognized in Indonesia. Customary law in Central Kalimantan is implemented by the existence of Dayak traditional institutions in Central Kalimantan which have been outlined in Central Kalimantan Province Regional Regulation No. 16 of 2008 and Central Kalimantan Governor Regulation no. 13 of 2009 concerning Dayak Traditional Institutions in Central Kalimantan. It is clear that customary law is a separate legal system so that it is different from other legal systems. The results of this research show that the consequences of divorce carried out by the Dayak traditional community are not only regulated by positive law in force in Indonesia, namely Law Number 1 of 1974 concerning Marriage, but are also regulated by Dayak customary law based on Regional Regulations. Kalimantan Province Regional Regulations. 16 of 2008 concerning Dayak Traditional Institutions in Central Kalimantan, there are Dayak customary punishments and marriage agreements carried out by parties from the Dayak traditional community.